Simulation and modeling methodologies, technologies and applications : 9th International Conference, SIMULTECH 2019 Prague, Czech Republic, July 29-31, 2019, Revised selected apers /: 9th International Conference, SIMULTECH 2019 Prague, Czech Republic, July 29-31, 2019, Revised selected apers. (2020) - Unknown
No abstract available